The first record of endangered Lycaena helle ([Denis & Schiffermüller], 1775) for Turkey (Lepidoptera: Lycaenidae) - S. S. Çalıskan; A. Hascenli (SHILAP, 2022)
Lycaena helle ([Denis & Schiffermüller],1775), is listed as “endangered” on the European Red List of butterflies. We report the first record of this species from Turkey. The EUNIS habitat information and photographs of the area where adult individuals was collected together with habitus dorsal and ventral photographs of the species were provided. The distribution status and habitat of the species in the Palaearctic region were evaluated.